Reconceptualising Australia’s transfer pricing rules: An approach based on adopting economic presence as a basis for taxation - Wilson-Rogers, Nicole; Pinto, Dale (University of New South Wales, Faculty of Law. Atax, 2015)
Against the background of a global focus on base erosion and profit shifting and well-publicised cases of high profile multinationals minimising their taxable burden in high tax jurisdictions, including the use of transfer pricing as a major tax minimisation strategy, this paper argues for a reconceptualisation of Australia’s Transfer Pricing rules by adopting an approach based on using economic presence as a basis for source based taxation.The approach of the paper is to first discuss and evaluate the evolution of Australia’s transfer pricing legislation. In this part, it will be argued that the most current reforms to Australia’s transfer pricing regime present several fundamental deficiencies. In response to these deficiencies, the second part of the paper advocates a policy response focused on a reconceptualised version of current source rules applying economic presence as a foundation for taxation.